Imagined Homeland: Inummariit as the Basis for the Concept of Inuit Nationhood - Nandori, Rita (Hungarian Journal of English and American Studies, 2021)
The Arctic is home to many distant and distinct Inuit communities and dialects. The strength of the Inuit originates in their being tethered to the same ancient narrative harkening back to common ancestral traditions, songs, and stories that characterize the Inummariit, the “real Inuk.” The wisdom of these traditions called quajimajatuqangit, or Inuit knowledge, is the key to creating nationhood among the Inuit via unikkausivut, sharing stories. This paper examines how affirming shared roots, common goals, and speaking with a united voice—the credo of the Circumpolar Council, the prime Inuit organization in the North—has helped establish an Inuit national identity for all Inuit living in several different regions and countries across the Arctic. In Canada, the creation of the semi-sovereign territory of Nunavut and the acknowledgement of the Inuit Nunangat, or homeland, have further aided the Inuit in redefining themselves. (RN)